The diversity of experimental organisms in biomedical research may be influenced by biomedical funding. (30th March 2017) - Erick Peirson, B. R.; Kropp, Heather; Damerow, Julia; Laubichler, Manfred D.
Abstract : Contrary to concerns of some critics, we present evidence that biomedical research is not dominated by a small handful of model organisms. An exhaustive analysis of research literature suggests that the diversity of experimental organisms in biomedical research has increased substantially since 1975. There has been a longstanding worry that organism‐centric funding policies can lead to biases in experimental organism choice, and thus negatively impact the direction of research and the interpretation of results. Critics have argued that a focus on model organisms has unduly constrained the diversity of experimental organisms. The availability of large electronic databases of scientific literature, combined with interest in quantitative methods among philosophers of science, presents new opportunities for data‐driven investigations into organism choice in biomedical research. The diversity of organisms used in NIH‐funded research may be considerably lower than in the broader biomedical sciences, and may be subject to greater constraints on organism choice. Abstract : Taxonomic diversity of experimental organisms in a sample of the biomedical research literature increased from 1975 through the late 1990s, and then plateaued. Articles citing NIH funding stopped diversifying earlier, but have resumed an upward trend in recent years. Use of NIH‐canonized model organisms may be on the decline.